Prototype Sistem Pendeteksi Longsor Berbasis Internet of Things Menggunakan Komunikasi Long Range (LoRa) - Lestari, Annisa Fitri; Riani, Erna; Nurjihan, Shita Fitria; Hasani, Rifqi Fuadi (Politeknik Negeri Jakarta, 2024)
Landslide disasters occur when materials such as rocks, debris, soil, or mixtures thereof move down a slope or out of the slope. As a natural disaster, landslides can cause material loss and loss of life. To reduce the impact, a system is needed that can monitor soil conditions continuously real-time and provide early warning to people living in landslide-prone areas. This designed system integrates a landslide-based detection tool Internet of Things (IoT) with Android applications. The system uses Realtime Database to store data from sensors, software Android Studio for developing Android applications, as well as communications Long Range (LoRa) to send sensor data to the microcontroller. This system can display data on soil moisture, rain intensity, vibration and conditions directly. If danger is detected, a buzzer will sound, and the application will send notifications quickly and precisely. Tests show that the sensor can transmit data using LoRa with an Received Signal Strength Indicator (RSSI) value of -71 dBm at 10 meters under conditions of Line of Sight, and up to 100 meters with an RSSI value of -106 dBm in the presence of obstructions. With this system, it is hoped that people in landslide-prone areas will be more alert, so that the risk of loss of life and material loss can be reduced.